The Use of Simulation in Nursing Education: An Assessment of its Effectiveness in Preparing Nurses for Clinical Practice - Jamal Siddiqui, Sarmad; Abbas Panhwar, Ghulam; Ullah Soomro, Saif; Ali Zardari, Javed; Wagan, Humera; Ali Naper, Mohammad (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: The objective of this research is to assess the effectiveness of simulation-based training in nursing education and its impact on the preparedness of nurses for clinical practice. Material and Methods: This quasi-experimental study was conducted on 70 study participants at the Benazir College for Nursing (BCON) at Shaheed Mohtarma Benazir Bhutto Medical University (SMBBMU) Larkana Sindh Pakistan. Individuals taking part in the medical-surgical nursing and critical care nursing classes. Suitable candidates were undergraduate nursing students currently include in the fundamental and advanced adult healthcare and critical care classes, aged 18 or older, and willing to participate in the research. However, students who had not undergone instruction in all simulators pertinent to the program prerequisites were not considered for the study. Results: A total of 70 participants were enrolled in the study. Out of them 11 (15.7%) participants were in the age group of <22, while 35 (50%) participants fell within the age range of 23-28, and 24 (34.2%) participants were >28 years old. In terms of educational level, 38 (54.2%) were at level 6, while 32 (45.7%) were at level 7. Before the intervention, participants rated their confidence in implementing repeated procedure tasks in the CSC at 2.85 ± 1.20. However, after the intervention, this rating significantly increased to 4.10 ± 0.54 (p<0.001). Participants reported using the skills learned in the CSC during their hospital rotations, with ratings increasing from 1.98 ± 0.75 to 4.12 ± 0.82. The CSC also had a positive impact on performance during clinical rotations, with a rating increase from 3.10 ± 0.65 to 4.10 ± 0.86. Participants expressed the opinion that certain skills could be better learned and practiced in a clinical area (CA), as indicated by the increase in ratings from 1.93 ± 0.98 to 3.98 ± 0.89. In terms of gender, males had a slightly higher mean score in self-efficacy (3.10 ± 0.15) compared to females (3.01 ± 0.14), although the difference was not statistically significant (p = 0.41). However, females had higher mean scores in both competency (4.10 ± 0.60) and communication (4.10 ± 0.34) compared to males (competency: 3.94 ± 0.15, communication. Practical implication: This research suggests simulation-based training is a valuable learning method for nursing students, enabling them to develop critical thinking, clinical reasoning, and effective communication skills in a controlled, safe environment. By rigorously evaluating the effectiveness of simulation-based learning, this research provides critical insights into educational strategies that enhance the clinical competencies of nursing students. As a result, nursing programs can refine their curricula to better prepare students for real-world clinical environments, ultimately leading to higher quality patient care and improved patient outcomes. Furthermore, the findings can inform policy-makers and educational institutions about the value of investing in simulation technology, fostering a more robust and adaptive healthcare workforce. By ensuring that new nurses are well-prepared through proven educational methods, the study supports a reduction in medical errors, increases the efficiency of healthcare delivery, and enhances overall patient safety. The community benefits from having access to better-trained nurses who can meet the increasing demands of modern healthcare settings, contributing to a healthier and more resilient population. Conclusion: The conclusions of this study indicate that simulation-based training provides a valuable learning experience for nursing students, allowing them to develop and refine crucial skills in a controlled and safe environment.